Porous supramolecularly templated optical resonators built in 1D photonic crystals - Hidalgo, Nuria (2011)
A synthetic route to attain photonic multilayers that presents controlled porosity only at the middle-layer level is shown. The spectral resonance associated with this porous layer shows strong sensitivity to the presence of vapors adsorbed or condensed within the void network, providing a potentially relevant material for gas detection. The importance of the interplay between pore and probe-molecule diameters is studied and its implications in size-selective detection are discussed. Controlled porosity: Photonic multilayers that presents controlled porosity only at the middle-layer level are herein introduced. The optical response of the ensemble shows strong sensitivity to the presence of vapors adsorbed or condensed within the void network, providing a potentially relevant material for gas detection.